Faktor penentu keputusan pemilihan sekolah taekwondo - Sukma, Heru Adde; Fatoni, Muhad (Universitas Hamzanwadi, 2023)
Problems in research studies on the sports service industry, understanding, achievement, image, and promotion determine school selection. This study aims to determine understanding, achievement, image, promotion determine the selection of taekwondo schools. This research method uses qualitative methods with a descriptive approach, the study population is representatives of trainers and 20 guardians of taekwondo students and data collection techniques by observation, interviews, questionnaires and documentation are then analyzed by data reduction, data presentation, conclusion and verification. With the results found that community taekwondo achievements require consideration of taekwondo schools that have achievements, it is hoped that the community by participating in taekwondo can have achievements. The community chooses a taekwondo school, it is necessary to consider a good school image, because it considers the child's character factor. Taekwondo promotions are carried out through individuals and taekwondo schools carry out promotions through social media such as instagram, facebook, whatsapp. the conclusion is that the election of the community has reasons in determining the selection of a taekwondo school, namely understanding, achievement, image and promotion determine the choice of the community to choose a taekwondo school.